The value relevance of published financial information : evidence from publicly traded firms on the Nasdaq OMX Iceland stock exchange - Gunnar Hákon Unnarsson 1998-; Hildur Inga Hauksdóttir 1999- (2021)
Valuation theory projects that there is a linear relationship between share price behavior and accounting measures. A vital objective in financial reporting is to provide investors with knowledge that is applicable for estimating a firm’s value. Research in the field of value relevance empirically analyzes whether this aim is met. This thesis attempts to recognize the quantitative factors that affect share prices for all listed firms on the Icelandic stock exchange over a ten-quarter period, from the third quarter of 2018 to the fourth quarter of 2020. Empirical analysis of a set of independent variables and a dependent variable is used to perform the study. The independent variables of interest in this thesis are return on equity, return on assets, debt-to-equity ratio, earnings per share and book value per share. In order to evaluate the effect of these variables on share price, three models were set up. The first, a pooled ordinary least squares regression, the second, a fixed effects model that took into account the individual firm fixed effects, and finally a model that followed the methodology introduced by Ohlson (1995). The results of the three models provide evidence that the study of accounting information proves to be beneficial for investors investing in firms listed on the Icelandic stock exchange, as the variables hold strong explanatory power.